Constructal design of forced convective flows in channels with two alternated rectangular heated bodies. (October 2018) - Feijó, B.C.; Lorenzini, G.; Isoldi, L.A.; Rocha, L.A.O.; Goulart, J.N.V.; dos Santos, E.D.
Highlights: Forced convective laminar flows in channels with two mounted alternately bodies was studied. Constructal Design and Exhaustive Search were used for geometric optimization of bodies. Main purposes were to maximize blocks heat exchange and minimize pressure drop in channel. The highest and lowest intrusion of the blocks benefited thermal and fluid dynamic purposes. The best design in multiobjective viewpoint was reached when two bodies were asymmetrical. Abstract: Present numerical study performs a geometrical optimization by means of Constructal Design and Exhaustive Search of two alternated rectangular heated bodies mounted in channel surfaces subjected to steady, two-dimensional, incompressible, laminar and forced convective air cooled flows. The problem has two purposes, maximize the heat transfer rate between the bodies and surrounding flow ( q ) and minimize pressure drop (Δ P ) in the channel, i.e., a multi-objective problem. The system is subjected to five constraints, but only two are evaluated here: area fractions of first and second bodies ( ϕ 1 and ϕ 2 ). The problem has two degrees of freedom: ratio between the height and length of upward and downward bodies ( H1 / L1 and H2 / L2 ) placed in lower and upper surfaces of the channel, respectively. The influence of fraction areas on the system performance is also investigated. All simulations are performed with constant Reynolds and Prandtl numbers, ReH = 100 and Pr = 0.71. As expected, highest intrusion and areas of the bodies were benefical for heat exchange, while the opposite was noticed for pressure drop. For multi-objective optimization, intermediate optimal shapes with assimetric sizes were achieved. The best multiobjective performance is reached for the upward body higher than the downstream one ( H 1 / L 1 > H 2 / L 2 ).